2022
DOI: 10.3390/ijerph192214670
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environmental Regulation, Industrial Structure, and Interaction on the High-Quality Development Efficiency of the Yellow River Basin in China from the Perspective of the Threshold Effect

Abstract: High-quality development efficiency can comprehensively measure the development quality of a region. This study constructed the SE-SBM Model and measured the quality development efficiency of the Yellow River Basin from 2010 to 2019. In panel regression, the periodic effects of industrial structure, environmental regulation, and their interaction terms on the efficiency of high-quality development are analyzed. From the perspective of the threshold effect, we explore the possible threshold of interaction to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Combing the above literature, it was found that the connotation of high-quality development has not formed a unified definition or concept, but these connotations have some common points: 1 ⃝ take the "five development concepts" as the basic principle and pay attention to the organic synergy of innovation, coordination, greenness, openness and sharing; 2 ⃝ adhere to the organic unity of the combination of scale, speed and quality benefits; 3 ⃝ taking "high quality" as the fundamental requirement, it should include micro service quality, meso industrial development, macroeconomic benefits and social welfare effects; 4 ⃝ follow the law of regional development and meet regional development goals; and 5 ⃝ take "meeting the people's growing needs for a better life" as the core goal. In addition, as reduction development is a new development idea, the connotation of reduction development has not formed a unified definition or concept, and there is no evaluation model for a high-quality development index system of the modern service industry under the background of reduction development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combing the above literature, it was found that the connotation of high-quality development has not formed a unified definition or concept, but these connotations have some common points: 1 ⃝ take the "five development concepts" as the basic principle and pay attention to the organic synergy of innovation, coordination, greenness, openness and sharing; 2 ⃝ adhere to the organic unity of the combination of scale, speed and quality benefits; 3 ⃝ taking "high quality" as the fundamental requirement, it should include micro service quality, meso industrial development, macroeconomic benefits and social welfare effects; 4 ⃝ follow the law of regional development and meet regional development goals; and 5 ⃝ take "meeting the people's growing needs for a better life" as the core goal. In addition, as reduction development is a new development idea, the connotation of reduction development has not formed a unified definition or concept, and there is no evaluation model for a high-quality development index system of the modern service industry under the background of reduction development.…”
Section: Discussionmentioning
confidence: 99%
“…However, the high-quality development of the modern service industry is not a simple scale expansion or speed improvement, but needs to achieve coordinated development in many aspects, such as the improvement in service quality [3], the enhancement of innovation ability [4], the optimization of industrial structure [5] and the improvement in resource utilization efficiency, while maintaining moderate growth. Therefore, how to accurately and comprehensively evaluate the high-quality development effect of the modern service industry under the background of reduction development has become an important issue to be solved in the current academic and practical circles.…”
Section: Introductionmentioning
confidence: 99%
“…As for research content, the evaluation of HQD has been involved in multiple industries, such as agriculture [37], logistics industry [38], tourism [39], with a significant focus on the economy [40], environmental constraints [41], and resources [42]. However, there is seldom a thorough attempt to estimate HQD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the study of high-quality development in the YRB, Xin and Liu [47] believed that the HQD in the YRB requires strict ecological comprehensive management, strengthening regional division of labor, promoting transportation infrastructure construction, and enhancing technological innovation capabilities. Li et al [48] explored the impact of industrial development on the ecological environment of the YRB and proposed the need to handle the relationship between the industrial development layout and the carrying capacity of river basin resources and the environment, to promote HQD. In a study of the HQD in the YREB, Zha et al [49] pointed out that specialized industrial agglomeration plays a vital role in promoting the quality of economic development.…”
Section: Literature Reviewmentioning
confidence: 99%